RBPs Play Important Roles in Vascular Endothelial Dysfunction Under Diabetic Conditions - Yang, Chunbo; Kelaini, Sophia; Caines, Rachel; Margariti, Andriana (Frontiers in Physiology, 2018)
Diabetes is one of the major health care problems worldwide leading to huge suffering and burden to patients and society. Diabetes is also considered as a cardiovascular disorder because of the correlation between diabetes and an increased incidence of cardiovascular disease. Vascular endothelial cell dysfunction is a major mediator of diabetic vascular complications. It has been established that diabetes contributes to significant alteration of the gene expression profile of vascular endothelial cells. Post-transcriptional regulation by RNA binding proteins (RBPs) plays an important role in the alteration of gene expression profile under diabetic conditions. The review focuses on the roles and mechanisms of critical RNA binding proteins towards diabetic vascular endothelial dysfunction. Deeper understanding of the post-transcriptional regulation by RBPs could lead to new therapeutic strategies against diabetic manifestation in the future.